(untitled) (Malaysian Journal of Civil Engineering, 2018)
The shear strength of rock discontinuities is an important parameter to consider in the stability analysis and design of engineering structures in rock masses, slopes, tunnels, open pit mine and foundations. In this study, the shear strength of rock discontinuities involving both bedding planes and joint surfaces at the Bakhtiary dam site was measured through 106 laboratory direct shear tests under the constant normal load (CNL) boundary condition. Also, the surface parameters of rock discontinuities for each test were specified, and shear strength of rock discontinuity was estimated by different empirical failure criteria. Finally, using different statistical approaches, the proper failure criteria for estimating the shear strength of rock discontinuities were proposed.